2017
DOI: 10.1136/bmjopen-2016-012822
|View full text |Cite
|
Sign up to set email alerts
|

Influence of psychological factors on the prognosis of chronic shoulder pain: protocol for a prospective cohort study

Abstract: IntroductionShoulder pain is a highly prevalent condition. Psychological factors could play an essential role in the prognosis of chronic shoulder pain (CSP). The aims of the study will be to analyse the level of association between psychological factors and pain-disability at baseline and prospectively to assess their prognostic role; to evaluate the association of pain catastrophising and kinesiophobia at baseline and prospectively in the relationship between pain intensity and disability, or between self-ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 60 publications
0
10
0
2
Order By: Relevance
“…Other biopsychosocial aspects were previously found to be altered in people with shoulder complaints, such as distorted sensory information, health-related quality of life, catastrophizing, worrying, somatization, anxiety and depression [ 7 , 8 , 9 , 19 , 28 , 29 , 36 , 106 , 112 ]. Although the predictability of some of them was related to shoulder prognosis, they were not different between individuals with acute and chronic RCRSP and none of them were selected by the tree as classifiers of these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other biopsychosocial aspects were previously found to be altered in people with shoulder complaints, such as distorted sensory information, health-related quality of life, catastrophizing, worrying, somatization, anxiety and depression [ 7 , 8 , 9 , 19 , 28 , 29 , 36 , 106 , 112 ]. Although the predictability of some of them was related to shoulder prognosis, they were not different between individuals with acute and chronic RCRSP and none of them were selected by the tree as classifiers of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Potential individuals were excluded for the following: body mass index above 28 kg/m 2 [ 40 ], history of fracture or surgery at the shoulder or cervicothoracic spine [ 29 ], signs of adhesive capsulitis (loss of more than 50% of passive range of motion in any direction) [ 2 , 41 ] or instability [ 42 ], cervical radiculopathy radiating to shoulder [ 2 , 43 ], physical therapy treatment or corticosteroid injection within 6 months prior to evaluation, history of cancer, neurologic, systemic, rheumatic or vascular disorder [ 2 , 44 , 45 ], cognitive impairments [ 45 ], use of psychiatric medication [ 46 , 47 ] or previous diagnosis associated with central sensitivity syndromes, as determined by part B of the Central Sensitization Inventory [ 48 ]. In central sensitivity syndromes, no specific organic cause can be found, and central sensitization is the root cause of the disorders [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between kinesophobia and other factors such as demographic characteristics, pain intensity, complaint duration, quality of life might be helpful for further interpretation and dealing with the fear and the musculoskeletal pain. Calderon et al 26 have stated that level of education may be a decisive factor in shoulder pain. Dunn et al 27 showed that pain was not related to rotator cuff tear severity but could be correlated with co-morbidities such as lower education level, and ethnicity.…”
Section: Discussionmentioning
confidence: 99%